Plaque Accumulation Beneath Maxillary All‐on‐4™ Implant‐Supported Prostheses. (27th January 2014) - Abi Nader, Samer; Eimar, Hazem; Momani, Moath; Shang, Ke; Daniel, Nach G.; Tamimi, Faleh
Abstract: Background: Maxillary prostheses supported by four implants, following the All‐on‐4™ principles, have become an accepted effective treatment for totally edentulous patients. Maintaining the hygiene of such fixed implant‐supported prostheses is challenging. Purpose: The purpose of this clinical study was to evaluate the distribution of plaque on the fitting surface of All‐on‐4 fixed prostheses in order to find new strategies for maintaining their hygiene. Materials and Methods: Twenty All‐on‐4 maxillary fixed prostheses collected from 20 patients, 6 months after delivery, were stained with methylene blue to disclose plaque accumulation at the fitting surfaces of the prostheses. Digital photographs of the fitting surfaces of the prostheses were recorded and processed. The distribution of accumulated plaque was evaluated statistically. Results: The average percentage of area covered with plaque was 28 ± 8% of the total area of the fitting surface of the prostheses. The fitting surfaces of the prostheses had three times more plaque on the palatal area (52.5 ± 7.33%) than on the buccal area (17.3 ± 7.33%, p < .05). The interimplant proximal areas of the fitting surface covered with plaque were high when the distance between implants was short ( r = −0.326, p = .014). Conclusion: These findings suggest that the hygiene of the All‐on‐4 prostheses could be improved by maximizing the distances between the inserted implants in the jaw, minimizing the prostheses' palatal extension and guiding patients to optimize their oral hygiene practices targeting the palatal area of their prostheses.